1972
DOI: 10.1104/pp.49.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ethylene in Phytochrome-mediated Carotenoid Synthesis

Abstract: Accumulation of carotenoid pigments in the shoot apex of etiolated pea (Pisum sativum cv. Alaska) seedlings is completely prevented by ethylene. Under certain conditions carotenoid synthesis is normally controlled by endogenously produced ethylene. The gas completely inhibits carotenoid synthesis induced either by continuous white light or brief illumination with red light, but only partially inhibits light-induced chlorophyll formation. Far red illumination followed by red illumination reverses the action of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

1973
1973
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 25 publications
2
8
0
1
Order By: Relevance
“…Our observed increase in ethylene production by sorghum tissue through an HIR response and the previously reported decreases Other workers have suggested that light control of ethylene production through the phytochrome system can intervene as a regulator of phytochrome control of plumular expansion (7), elongation of coleoptiles (13), hook opening (12), and formation of carotene (11). In all of these cases, there is a decrease of ethylene production by plant tissue under red light.…”
Section: Resultssupporting
confidence: 66%
“…Our observed increase in ethylene production by sorghum tissue through an HIR response and the previously reported decreases Other workers have suggested that light control of ethylene production through the phytochrome system can intervene as a regulator of phytochrome control of plumular expansion (7), elongation of coleoptiles (13), hook opening (12), and formation of carotene (11). In all of these cases, there is a decrease of ethylene production by plant tissue under red light.…”
Section: Resultssupporting
confidence: 66%
“…It has recently been reported that light inhibits ethylene production in segments of green oat leaves but not in etiolated leaves (7). The experiments dealing with the effect of monochromatic light on plant tissues suggest an inhibitory effect of red light as compared to darkness on the rate of ethylene production (8,11,12,18). However, Janes et al (10) found no effect of red light on the rate of ethylene production in the intact lettuce seedlings.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, it is of interest to ask whether inhibition of ethylene production might be responsible for the red light-induced enhancement of phototropic curvature in the pea seedling. If a response induced by red light is indeed mediated by inhibition of ethylene production, it can be mimicked by placing the responsive plant or tissue under hypobaric conditions where diffusive escape of ethylene is greatly enhanced (8,9,11,12). Phototropic behavior of the etiolated pea seedling is not affected by hypobaric treatment (data not shown), suggesting that changes in endogenous ethylene are not involved in red light enhanced-phototropic curvature in clear distinction from the mechanism of red light enhancement of geotropism (9).…”
Section: Resultsmentioning
confidence: 96%
“…Yet the mechanism by which red light enhances phototropic curvature development in etiolated pea seedlings is distinct from that by which it promotes geotropism (9) and other photomorphogenic processes where ethylene plays a regulatory role (8,9,11,12). This conclusion is based on the facts that (a) the time course for the red light action on blue light-induced phototropism (Table I) does not parallel that on geotropism and ethylene production (9); (b) hypobaric treatment does not affect phototropism whereas it does other ethylene-related photomorphogenic responses including geotropism (8,9,11,12); (c) ethylene inhibits gravity-induced downward migration of auxin (5), but has no effect on photoinduced lateral auxin movement (Table III). In geotropism, ethylene was suggested to act on a process intervening between the perception of gravity and the lateral movement of auxin (13), and thus has no direct action on the lateral auxin transport system itself either for geotropism or phototropism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation